Assessment on infection prevention and control knowledge among medical professionals in south Indian population - Rahul Radhakrishnan; Maheswary Datchanamoorthy; Damodharan Narayanasamy; Kakithakara Vajravelu Leela (Journal of Infection in Developing Countries)
Introduction: Healthcare workers are always at higher risk of biological exposure as the healthcare setting is hazardous, and it is impracticable to exclude infection. Poor compliance with standard precautions among healthcare workers is one of the leading causes of healthcare-associated infections. This study analyzed the gaps in knowledge, attitude, and practice of infection control among healthcare workers and the influence of the COVID-19 pandemic, internet, and social media usage on infection control.